Earthquake resilience among apartment and flat communities: a qualitative study in Jakarta, Indonesia - Fatmah, Fatmah; Fitrinitia, Irene Sondang; Gao, Liang (Frontiers in Built Environment, 2026)
BackgroundEarthquakes present serious risks for residents living in vertical housing structures such as apartments and flats complexes in Jakarta. Although earthquake preparedness and mitigation programs have been introduced by governmental and non-governmental organizations, their implementation remains sporadic. Consequently, there is limited insight into how communities perceive, interpret, and apply these measures in everyday disaster preparedness practices. This study explores earthquake management practices among resident associations and building managers in the selected apartment and flat in Jakarta.MethodsUsing a cross-sectional qualitative design, data were collected through five Focus Group Discussions (FGDs) with residents, five in-depth interviews with building managers, and two in-depth interviews with key stakeholders.ResultsThe study found that all flats lack formal Standard Operating Procedures (SOPs), written earthquake preparedness guidelines, and SLF certification for earthquake-resistant strength, except for one apartment. Government institutional capacity, including FPRB and inter-institutional collaboration, is key to coordinating disaster management, but budgets often prioritize general disaster management over earthquake-specific preparedness. Despite these gaps, residents show good preparedness through prompt evacuation, supported by social networks, though participation varies due to emotional responses. Lack of standardized Earthquake Early Warning System (EEWS) procedures and limited earthquake simulations leave residents largely untrained and evacuation management weak. However, resident association such as neighbourhood units (RT), community units (RW), Tenant Safety Officers (TSOs), P3SRS play an important role in organizing evacuation, coordinating emergency responses, and supporting recovery activities to strengthen earthquake resilience.ConclusionThis study highlights the importance of empowering Tenant Safety Officers (TSOs) and P3SRS in apartment buildings, and RT/RW in flats to prepare earthquake preparedness standard operating procedures (SOPs) based on guidance from government institutions, the private sector, and non-governmental organizations.